The use of vascular plants as traditional boat raw material by Yachai tribe in Mappi Regency - SERLLY LANOEROE; ELISA MARKUS KESAULIJA; YOHANES YOSEPH RAHAWARIN (Society for Indonesian Biodiversity, 2005)
This research is executed aim to know the plant species and the way of exploiting permanent wood upon which traditional boat making by Yachai tribe in Mappi regency. The Method that used in this research is descriptive method with the structural semi interview technique and direct perception in field. Result of research indicate that the tribe Yachai exploit the plant species have permanent wood upon which traditional boat as much 26 species from 14 family. There are 8 wood species which is often used for the body of boat and also own the good quality according to Yachai tribe, that is Atam (Scihizomeria serrata Hochr), Batki (Adinandra forbesii Baker. F), Chomach (Gordoniapapuana Kobuski), Rupke (Tristania sp.), Bao (Dillenia papuana artelli), Top (Buchanania macrocarpa Laut), Mitbo (Cordia Dichtoma Forst.), and Yunun (Camnosperma brevipetiolata Volkens). While to part of oar exploit 2 wood species that is Bach (Buchanania Arborescens.Bi) and Tup (Litsea ampala Merr). Yachai Tribe recognized 3 boat model owning different size measure and function, that is Junun Ramchai, Junun Pochoi and Junun Toch.Â© 2005 Jurusan Biologi FMIPA UNS SurakartaKey words: vascular plants, traditional boat, Yachai tribe, Mappi Regency.